DEVELOPMENT OF MAGNETIC ROULETTE MEDIA BY USING DISCOVERY LEARNING FOR THE INTRODUCTION OF SYMBOLS 1-10 IN CHILDREN AGED 4 - 5 YEARS AT HIDAYATUS SHIBYAN KINDERGARTEN SURABAYA - Bakrisuk, Fidya Salim; Setyowati, Sri; Khotimah, Nurul (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2025)
Activities Based Contemporary (PABC) learning model on gross motor skills, especially balance, and learning concentration in children aged 4-5 years. The background of the study shows that there is a high percentage of children aged 4-5 years at Al Irsyad Kindergarten, Banyuwangi Regency who have less than optimal balance (74.5%) and learning concentration (71.1%). This is identified as one of the reasons for the tendency of children to spend more and more time with passive activities in front of the screen of gadgets. This study uses a quantitative approach with a design that involves statistical tests to measure the influence of PABC. The subjects of the study were children aged 4-5 years at Al Irsyad Kindergarten Banyuwangi. Data were collected through observation using motor ability and concentration observation sheets. Data analysis includes normality tests, homogeneity tests, validity tests, reliability tests, as well as Independent Sample T-Test and Paired Sample T-Test. The PABC model itself is an integration of physical activity with contemporary elements that are relevant to children, emphasizing freedom of movement, self-expression, and the use of games as a fun and effective learning method. Its implementation is manifested in a series of physical obstacles such as "Army Tunnel", "Obstacle Jump", "Rocking Bridge", and "Sniping Target", and uses the syntax of the AREK method (Observe, Plan Action, Exploration, Communication). The results of this study are expected to provide empirical evidence on the contribution of PABC in improving gross motor skills and early childhood learning concentration, as well as providing a scientific basis for the development of innovative learning programs that are in accordance with the needs of children's development in the digital era.